Evaluation of in vivo digestibility in rabbits using Tithonia diversifolia as partial replacement of the concentrate (Revista Sistemas de Producción Agroecológicos, 2019)
The production of rabbits in Colombia is a production system little exploited so far, but day by day it has been gaining momentum due to the ease of its establishment, its high production rates and its great nutritional contribution to human food, but its establishment in the country has been hampered by the high costs of the inputs used for its food, since the vast majority are imported and used for the production of concentrates, for this reason it is necessary to seek feeding strategies that satisfy the nutritional requirements of animals and that are easily accessible and economical for the producer. The objective of this study was to evaluate in vivo digestibility in rabbits using Tithonia diversifolia as a partial replacement for the concentrate, using as evaluation parameters the percentage of total digestible nutrients (TND), digestibility coefficients (DCO) of crude protein (PC) , crude fiber (CF), ether extract (EE) and non-nitrogenous extract (NNE); digestible energy (DE) and metabolizable energy (ME) ) for each of the treatments; using as experimental unit, 24 rabbits with an average weight of 2 kg ± 300 gr, distributed by a completely random design, as follows, T0 was the control, with basal diet 100% concentrate; T1 replacement of 10% of the concentrate by Tithonia diversifolia; T2 replacement of 20% and T3 replacement of 30%. From where it was concluded that the inclusion of Tithonia diversifolia in all treatments, presented a contribution of nutrients consistent with what is required by rabbits and these nutrients presented good digestibility, which constitutes an alternative food resource in their diet in tropical conditions. in order to reduce production costs and maintain yields.
Keywords: Asteraceae; in vivo digestibility; concentrates; rabbits